Relationship with the Regularity of Visits Complications of Hypertension in Patients more than 45 Years Old - Wahyu Wijayanto; Prijono Satyabakti (Jurnal Berkala Epidemiologi, 2014)
Hypertension is a risk factor for various degenerative diseases, including coronary heart disease, stroke, and other vascular diseases. One of the risk factors that can increase hypertension is a poor lifestyle such as smoking, excessive salt consumption in food, and lack of exercise. This research was conducted to determine the relationship of the level of knowledge about hypertension complications with regular visits to patients with hypertension aged 45 years and over at the Public Health Center (PHC) of Tembok Dukuh, Surabaya. This type of research is observational with cross-sectional research design. The sample size was 48 people, namely hypertension patients aged 45 years and over who were taking treatment at PHC of Tembok Dukuh. The independent variable is the patient's knowledge of hypertension complications and the dependent variable is the regularity of the hypertension patient's visit to the PHC of Tembok Dukuh. Data analysis uses cross-tabulation. The results of the study with cross tabulation showed that 30 people from 48 respondents have less knowledge and affect the regularity of visits to the PHC of Tembok Dukuh. The conclusion that can be drawn is that most of the hypertensive patients aged 45 years and over who visit the PHC of Tembok Dukuh have less knowledge about the complications of hypertension which results in regular visits by hypertensive patients.